Gender differences in experimental wage negotiations - Marcus Dittrich; Andreas Knabe; Kristina Leipold (Center for Economic Studies and ifo Institute (CESifo), 2012)
We examine behavioral gender differences and gender pairing effects in a laboratory experiment with face-to-face alternating-offers wage bargaining. Our results suggest that male players are able to obtain better bargaining outcomes than female players. Male employees get higher wages than female employees. Male employers pay lower wages to female employees than female employers pay to male employees. Moreover, we find gender differences in the first offers of the bargaining game.
Keywords: C72; C91; J16; 330; gender differences; wage bargaining; labor market experiment; Lohnverhandlungen; Verhandlungstheorie; Geschlecht; Fraueneinkommen; Lohndifferenzierung; Test